Empowerment of Housewives Through Financial Management Education as a Solution to Economic Challenges - Juliati, Selina Nova; Herliana, Ariska; Hanisah, Isnaeni Hasna; Perwithosuci, Winny (TAAWUN, 2025)
The purpose of this community service program is to improve family financial management for housewives in Dukuh Samber, Sabrang Lor Village, Trucuk District, Klaten Regency. Community service activities are carried out in two stages, namely socialization regarding family financial management and basic training in recording financial allocations. Socialization aims to provide basic understanding, while basic training in recording financial allocations is designed to build practical skills in managing finances. The methods used include interactive lectures, group discussions, and direct practice of budget recording. This activity involves pre-tests and post-tests to measure the increase in participants’ understanding. The results of the activity showed that 97.13% of participants understood the family financial management material presented, as evidenced by changes in knowledge after participating in the socialization. Through basic financial recording training, participants can make family budget records wisely. With this community service, housewives in Dukuh Samber can apply their knowledge to optimally increase their family income which will reduce dependence on high-interest debt. In addition, this activity also has a long-term impact in the form of increasing the welfare of the Dukuh Samber community.